Analisis Struktur Industri Telepon Seluler Di Indonesia - Ananta Heri Pramono (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2010)
In the recent year, the cellular telephone industry in Indonesia has been growing rapidly. This can be seen from the increasing number of their customer for the past five years. With using five forces model analysis, identification driving forces, key success factors, and industry characteristic, the author came up with a conclusion that the cellular telephone industry in Indonesia recently possesses high attractiveness, promising profitability and for the same time also having a high intensity of competitiveness. The decree No. 36/1999 which is made to deregulate Telecommunication Industry and fast moving of the cellular telephone technology were driving forces factors. Holding a large funding and having a high capability in cellular technology were the key success factors to triumph this sector.